2018
DOI: 10.1111/irv.12544
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of seasonal influenza in the Middle East and North Africa regions, 2010‐2016: Circulating influenza A and B viruses and spatial timing of epidemics

Abstract: BackgroundThere is a limited knowledge regarding the epidemiology of influenza in Middle East and North Africa.ObjectivesWe described the patterns of influenza circulation and the timing of seasonal epidemics in countries of Middle East and North Africa.MethodsWe used virological surveillance data for 2010‐2016 from the WHO FluNet database. In each country, we calculated the median proportion of cases that were caused by each virus type and subtype; determined the timing and amplitude of the primary and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 32 publications
16
50
1
Order By: Relevance
“…We observed respiratory viral activity throughout the study period with defined peaks for multiple viruses, including influenza virus, which had higher activity between November and December. This is similar to what have been reported in other countries with similar climate around the Arabian Peninsula [4]. In addition, our data identified another major peak of influenza activity between January and March of 2012, which is interestingly similar to what have been reported in Northern Hemisphere countries around the same time [4].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We observed respiratory viral activity throughout the study period with defined peaks for multiple viruses, including influenza virus, which had higher activity between November and December. This is similar to what have been reported in other countries with similar climate around the Arabian Peninsula [4]. In addition, our data identified another major peak of influenza activity between January and March of 2012, which is interestingly similar to what have been reported in Northern Hemisphere countries around the same time [4].…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to what have been reported in other countries with similar climate around the Arabian Peninsula [4]. In addition, our data identified another major peak of influenza activity between January and March of 2012, which is interestingly similar to what have been reported in Northern Hemisphere countries around the same time [4]. Nonetheless, in this current study, influenza A subtyping was not routinely performed between 2012-2016.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is of paramount importance to determine the timing of influenza circulation for each region in order to decide on the best timing for vaccine delivery, aid healthcare workers in their clinical management of suspected cases in addition to increasing emphasis on prevention of infection and control of transmission [76]. In his review of surveillance data from the MENA region for the time period 2010-2016, Caini et al reported that most of the region's countries had a primary peak between January and March with no or barely noticeable secondary peaks [77]. According to the Lebanese SARI sentinel surveillance, the primary peak extended from January till mid of March [37].…”
Section: Discussionmentioning
confidence: 99%